Emended description and resurrection of Kadsura matsudae (Schisandraceae) - Suetsugu, Kenji; Hsu, Tian-Chuan; Toma, Tsugutaka; Miyake, Takashi; Saunders, Richard M. K. (Phytotaxa, 2017)
The taxonomic identity of Kadsura matsudae is reevaluated. This taxon is often treated as a synonym of K. japonica, a species known from Japan, Korea, and Taiwan. When studying the type materials of K. matsudae, however, we noted that some of its morphological characters, such as the non-contiguous thecae in adjacent stamens, do not fall within the typical variation range of K. japonica. Phylogenetic analysis suggests that although K. matsudae is retrieved within the sect. Kadsura clade, it is not closely related to K. japonica. We therefore propose that K. matsudae should be recognized as a distinct species. Because the protologue of K. matsudae lacks sufficient detail with regards to stamen morphology, which is one of the most important characteristics for identifying the species, we provide an emended description of K. matsudae based on the holotype specimen and newly collected specimens.